Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2003
DOI: 10.1128/aac.47.12.3945-3949.2003
|View full text |Cite
|
Sign up to set email alerts
|

MolecularEpidemiology of orf513-Bearing Class 1 Integrons in MultiresistantClinical Isolates from ArgentineanHospitals

Abstract: The spread of orf513-bearing class 1 integrons is associated with bla CTX-M-2 in gram-negative clinical isolates in Argentina, with In35 being the most frequently found integron (74%). Among 65 isolates without bla CTX-M-2 , only one harbored a novel orf513-bearing class 1 integron with the dfrA3b gene. The finding of orf513 not associated with class 1 integrons in two gram-positive strains indicates the widespread occurrence of this putative site-specific recombinase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 21 publications
3
26
0
Order By: Relevance
“…It therefore seems likely that the associated ISCR1 element was involved in sequestering this section of DNA from the chromosome of K. ascorbata or a near relative into a (62), and in Morganella morganii (78). In addition, bla CTX-M2 has also been found in isolates of the gram-positive species Enterococcus faecium and serogroup G Streptococcus agalactiae (2), again in close association with ISCR1.…”
Section: Iscr1mentioning
confidence: 93%
See 1 more Smart Citation
“…It therefore seems likely that the associated ISCR1 element was involved in sequestering this section of DNA from the chromosome of K. ascorbata or a near relative into a (62), and in Morganella morganii (78). In addition, bla CTX-M2 has also been found in isolates of the gram-positive species Enterococcus faecium and serogroup G Streptococcus agalactiae (2), again in close association with ISCR1.…”
Section: Iscr1mentioning
confidence: 93%
“…The novel trimethoprim resistance gene dfrA23 was found on a nonconjugative plasmid, t-st4, of 110 kb in S. enterica serovar Typhimurium from Italy (104); dfrA18 was found on the incC group plasmid pDG0100 (93) and on a conjugative incF1 plasmid of 140 kb in S. enterica serovar Typhimurium from Albania (102); and dfrA10 was found in In34 (71) and as a component of two variants (SGI1A and SGI1D) of the Salmonella genomic island SGI1 on the chromosome of Salmonella enterica serovar Agona (see below) (15). The dfrA3b gene was found linked to ISCR1 in the C. freundii isolate from Argentina (2).…”
Section: Iscr1mentioning
confidence: 99%
“…The combination of bla CTX-M-2 linked to ISCR1 is common in clinical isolates from South America (3,4,35,50), and this resistance gene encodes 69% of the extended-spectrum ␤-lactamases found in clinical isolates from Argentinean hospitals (3). Since a bla CTX-M-2 gene linked to ISCR1 was present in strain 12863, we designed primer pairs HS819/HS820, specific for ISCR1, and HS856/HS857, specific for bla CTX-M-2 (Table 1), and screened all 21 class 1-positive strains for their presence.…”
Section: Resultsmentioning
confidence: 99%
“…Almost all open reading frame (orf) 513-bearing class 1 integrons are associated with bla CTX-M-2 in the Gram-negative bacterial population under study and the sequences adjacent to the bla CTX-M-2 gene are conserved in all the studied isolates. 33) Eckert et al 34) examined the bla CTX-M genes in E. coli and K. pneumoniae by cloning, sequencing, and PCR analysis and detected a complex sul1-type integron including an orf513, that carried the bla gene together with its surrounding DNA. We found that 60% of intI1-positive isolates also contained the sul1 gene (data not shown).…”
Section: Discussionmentioning
confidence: 99%